False Dawns and New Horizons in Patient Safety Research and Practice - Mannion, Russell (Int J Health Policy Manag, 2017)
In response to a weight of evidence that patients are frequently harmed as a result of their care, there have been concerted efforts to make healthcare safer, with health systems across the globe investing significant resources in policies and programmes designed to reduce adverse events. Yet, despite extensive efforts, improvements in safety have proved difficult to sustain and spread, with studies confirming there has been no measurable, systems-level improvement in the overall rates of preventable harm. Here, we highlight the limitations of the thinking which underpins current efforts to make healthcare systems safer and point to new and emerging approaches to understanding and addressing patient safety in complex, dynamic health systems.